Content Validity and Reliability of The Inter-Rater Instrument for Android-Based Speaking Performance Assessment - Triwibowo, Febri Dhany; Rusilowati, Ani; Linggar Bharati, Dwi Anggani (Journal of Research and Educational Research Evaluation, 2020)
This research is part of development research based on problems encountered in the field, which is the absence of an android-based speaking assessment instrument and one that supports one of the conservation values of Semarang State University, which is paperless. The aim of this study was to show the results of the validity and reliability test of the developed android-based speaking performance assessment instrument. The research method used is quantitative description of 3 expert judgments. The validation instrument developed in the form of an expert assessment sheet with 4 criteria, there are ease of use, visuals, content, and benefits. Analysis of the content validity of the assessment sheet using the V coefficient by Aiken and the reliability of the instrument content using the Interclass Correlation Coefficient (ICC) analysis with the help of SPSS version 16.0. The results showed valid results with all criteria valued> 0.3, namely with the lowest index 0.8 and the highest 1.0. Inter-rater reliability test using ICC obtained a value of 0.875, which means that all the criteria for the developed android-based speaking performance assessment instrument have a good level of consistency. Based on the results, it can be showed that the android-based speaking performance assessment instrument can be used.